Quem sou eu: autorrepresentações de travestis no orkut - LIMA, Aline Soares (2009)
This study investigates the self representations of transvestites in orkut and constitutive elements of their (cyber)identities, having the visuality as the focus and determinant axis. For this, the emphasis is given to pictures and self portraits, present in albums of their profiles on the site. We are interested in understanding what is the image they construct of themselves from physical reconstructions, aesthetic formulations, costumes, scenery, performances and a whole network of symbolic meaning which is important for them. Orkut, like many other social environments of the internet, comprehends speeches and narratives of individuals and social groups that describe, identify and represent themselves of the most varied ways and with the most diverse goals and interests. In order to understand how the self representations of transvestites are built on orkut, it was investigated initially some communities with trans thematic, then it was selected the profiles of two transvestites, with whom interviews were also conducted. Although this study focuses on the self representations in the orkut, other environments in cyberspace have been researched, as blogs and sites for transvestites. We conclude that there are multiple ways to represent transvestitely, not just the stereotypical, stigmatized and marginalized representations widespread by the media